The Role of Self Efficacy and Self-Esteem in Improving Academic Performance Amongst Aviation Polytechnic’s Students - Prabowo, Achmad Setiyo; Nurlaela, Luthfiyah; Ekohariadi; Buditjahjanto, Asto; Yundra, Eppy (Journal of Technical Education and Training, 2021)
Quality education plays a role in supporting the creation of smart and competitive individuals in the era of globalization. To achieve good academic achievement, belief in his abilities is a crucial attitude which is in this case, is known as self-efficacy. The purpose of this study is to analyze the influence of self-efficacy and self-esteem on the academic performance amongst the Aviation Polytechnic’s students. This study is a causal research with a quantitative approach—sampling using total sampling techniques, resulting in the number of samples taken as many as 195 cadets. Collecting data in this study is by distributing questionnaires. The data analysis technique used is PLS. The results of the study proved that: (1) there is a significant influence between Self-Esteem and Self-Efficacy; (2) there is no significant influence between Self-Esteem Academic Performance; and (3) there is no significant influence between Self-Efficacy and Academic Performance. These findings indicate that the absence of Self-Esteem or Self-Efficacy cannot necessarily shape academic performance.